SISTEM PEMANTAUAN SISA PAKAN, PENJADWALAN PEMBERIAN PAKAN DAN PENGGANTIAN AIR PADA PENAMPUNGAN IKAN CUPANG BERBASIS IOT DAN BLYNK - Damar, Raden Ario; Setiyadi, Didik (ISTEK WIDURI, 2021)
Currently, the monitoring system for leftover feed, feeding scheduling and water replacement at betta fish shelters is still human-oriented or can be said to be manual by going to fish shelters, then taking fish feed shelters and then sprinkling the fish feed using the hand of the fish owner himself into the fish shelter, at the same time seeing the last condition of the rest of the fish feed, besides replacing the water in the fish shelter, it is still done by manually moving the fish first to the reserve reservoir after that replacing the existing water in the fish tank. shelter used. Because the betta fish owners who have a lot of activities make the betta fish owners become disturbed in terms of feeding and water replacement in fish shelters that become irregular with a predetermined schedule, as well as monitoring the remaining fish feed in fish feed shelters. This can be an obstacle in the maintenance of betta fish which makes the development process of betta fish disturbed so that it can be one of the factors that cause betta fish to stress, get sick or even die. The prototype tool for monitoring feed, scheduling feed distribution and changing water in betta fish reservoirs using several tools, namely the Arduino Uno microcontroller, Servo motor actuator SG-90, mini submersible water pump, ultrasonic sensor HC-SR04, Blynk application which is used as a tool that can be controlled via a smartphone for automation of feeding, water replacement, in addition to monitoring the remaining fish feed in betta fish shelters.